Peningkatan Kompetensi Calon Guru PAUD dalam Melakukan Asesmen Motorik Kasar Anak melalui Pelatihan dan Pendampingan Berkesinambungan - Alim, Melvi Lesmana; Joni, Joni; Fauziddin, Mohammad; Ahmadi, Dedi (Jurnal Pengabdian Masyarakat (ABDIRA), 2025)
Early Childhood Education (ECE) plays a critical role in laying the foundation for holistic child development, including gross motor skills. Teachers’ competence in assessing gross motor development is essential for early identification of developmental needs. This article explores the role of continuous training and mentoring in enhancing the assessment competence of prospective ECE teachers. Utilizing an educational action research approach, the program involved interactive training and eight weeks of field mentoring. Results show significant improvement in participants’ knowledge, technical assessment skills, and professional attitudes. The program demonstrates the effectiveness of combining theory and practice through experiential learning, scaffolding, and systematic reflection in developing adaptive and reflective early childhood educators.